2015
DOI: 10.1097/ico.0000000000000544
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Corneal and Anterior Chamber Parameters Derived From Scheimpflug Imaging in Arab and South Asian Normal Eyes

Abstract: Normal eyes of Arab ethnicity tend to have statistically thicker and flatter corneas and less-crowded anterior segments than those of the South Asian counterparts. These epidemiological differences have a mild to moderate biological effect size (Cohen d), but they should be considered when evaluating these eyes for anterior segment or corneal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In other words, in our study, mixed race and Caucasian individuals have steeper corneas than African Black individuals, even though corneal astigmatism was comparable. Differences in corneal power, without differences in corneal astigmatism have previously been described when comparing ethnic groups 4,6,8 . However, other studies found differences in corneal power between ethnic groups 5,7 This is the rst study looking at corneal astigmatism among people of African Black, Mixed Race, and Caucasian descent, which is its main strength.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In other words, in our study, mixed race and Caucasian individuals have steeper corneas than African Black individuals, even though corneal astigmatism was comparable. Differences in corneal power, without differences in corneal astigmatism have previously been described when comparing ethnic groups 4,6,8 . However, other studies found differences in corneal power between ethnic groups 5,7 This is the rst study looking at corneal astigmatism among people of African Black, Mixed Race, and Caucasian descent, which is its main strength.…”
Section: Discussionmentioning
confidence: 82%
“…A margin of equivalence of 0.30 was used for the pairwise comparisons. The equivalence margin of 0.30 was based on clinical reasoning and previous research that showed a mean difference varying from 0.1 to 0.3 between ethnic groups 4,15,16 . A standard deviation of 1 was used for corneal astigmatism magnitude.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Furthermore, the mean ACD in our sample was higher than the mean reported by Feng et al, 19 )3.25 mm -3.11 mm(, but it fell within the normal variations recorded for numerous population groups. Likewise, higher mean corneal thickness and ACD values were observed in Arabs compared to South Asian eyes in a study conducted by Parkash et al, 24 who looked at the differences in the anterior segment measurements between these 2 groups. Evaluating the differences in these parameters between the various Arab countries would be an interesting area for future studies.…”
Section: Discussionmentioning
confidence: 90%